Outcomes of Surgical Treatment for Localized Tenosynovial Giant-Cell Tumor of the Foot and Ankle: A Case Series - Ipponi, Edoardo; Ruinato, Alfio Damiano; Lombardi, Leonardo; Cordoni, Martina; De Franco, Silvia; D'Arienzo, Antonio; Andreani, Lorenzo (Acta medica Lituanica, 2023)
Background: Giant cell tumor of the tendon sheath (GCTTS), also termed Tenosynovial giant cell tumor (TGCT), is a locally aggressive tumor which originates from tendon sheaths or bursas. Around 3–5% of these tumors arise from foot and ankle. Localized lesions in this area are often manifested as firm masses or nodules with slow but continuous progression through months and years. Pain associated with weight-bearing, as well as limitations in joint motions, may be reported, depending on tumor’s location. Surgery is the treatment of choice for the definitive removal of GCTTSs with the aim to eradicate the neoplasm and restore the lower limb’s functionality.Methods: Thirteen cases suffering from GCTTS of the foot and ankle underwent surgical resection at our institution between 2017 and 2022. For each case we recorded pre-operative and post-operative symptoms, as well as their pre-operative and post-operative functional status according to both MSTS and AOFAS scores. Eventual complications and local recurrences were reported.Results: Each patient experienced an at least mild pain before surgical treatment. The mean pre-operative MSTS and AOFAS scores were 22.8 and 70.7, respectively. The mean tumor size was 17.7 mm. Each patient received a resection with wide margins. Two cases (15.4%) had local recurrences. None had major complications at their latest follow-up. After the surgery, the mean post-operative MSTS and AOFAS scores increased to 28.3 and 92.2, respectively.Conclusion: Resection with wide margins for foot and ankle GCTTS is effective in restoring the patients’ lower limb functionality and is associated with reasonable local recurrence rates.
Keywords: Tenosynovial giant cell tumor; Giant cell tumor of the tendon sheath; foot; ankle; resection; functionality; AOFAS